2019
DOI: 10.1177/0020764019882709
|View full text |Cite
|
Sign up to set email alerts
|

Functioning in community-dwelling patients with schizophrenia spectrum disorders in rural Greece

Abstract: Background: There is a dearth of studies on functioning in patients with psychotic disorders in rural areas. Aim: The objective of this study was to assess functioning in a population-based sample of patients with psychotic disorders who live in rural, remote and deprived areas in Greece, and to explore the differences in functioning across ages. Methods: The sample consisted of 61 patients with psychotic disorders that were engaged to treatment with a community mental health service. The mean age of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Finally, the measurement of other aspects of patients' outcome, such as psychopathology and functioning, were beyond the scope of this study. These issues have been recently addressed by other research by our team and results were encouraging (Peritogiannis et al, 2019;Peritogiannis & Nikolaou, 2020).…”
Section: Strengths and Limitationsmentioning
confidence: 57%
“…Finally, the measurement of other aspects of patients' outcome, such as psychopathology and functioning, were beyond the scope of this study. These issues have been recently addressed by other research by our team and results were encouraging (Peritogiannis et al, 2019;Peritogiannis & Nikolaou, 2020).…”
Section: Strengths and Limitationsmentioning
confidence: 57%
“…In a study in Denmark on an incidence cohort of FEP patients, 34% of the patients achieved symptomatic remission after a follow-up period of 4–18 years, whereas functional remission was observed in 41% of the patients (Klærke et al, 2019). Also, a recent study in rural Greece found that 29.5% of a sample of chronic patients with schizophrenia spectrum disorders were symptomatically remitted, but the percentage of adequately functioning patients was somewhat higher (37.7%) (Peritogiannis & Nikolaou, 2020).…”
Section: Outcome In Terms Of Symptomatology and Functioningmentioning
confidence: 99%
“…Importantly, these findings are compatible with the results of an earlier study in Australia, which suggested that the outcome of rehabilitation intervention for chronic severe mental disorders was better in rural communities (Tirupati et al, 2010). Other recent studies that have addressed the outcomes of patients with psychotic disorders in rural areas are small and uncontrolled, and, although their findings are promising, they are still inconclusive (Peritogiannis et al, 2019; Peritogiannis & Nikolaou, 2020).…”
Section: Discussionmentioning
confidence: 99%